Pengembangan Sistem Pengukuran Gejala Fisis Longsor Sistem Elektronik Dan Optik - Widiyatmoko, Bambang; Hanto, Dwi; Puranto, Prabowo (BERKALA FISIKA, 2010)
Landslides are a common disaster in Indonesia so that the necessary anticipation through the monitoring of areas prone to the development of instrumentation systems disaster. Design has been done measuring the physical symptoms of landslides using optical and electronic systems. Measured physical symptoms include a shift in soil, and soil strains. Shift in the electronic ground sensors made by using linear and potensio constan current source. The result of measurement is known that this sensor can detect a shift change of 0.5 mm with a maximum shift of 250 mm. Soil strain measured using a fiber optic brag grating (FBG), which changes the transmission peak of FBG was done by using the diode laser wavelength sweeping. Fiber brag grating is an optical sensor that works according to the resonant effect of a refractive index grating lattice, where the resonant wavelength is determined by the lattice distance. From this principle it is when the lattice spacing change due to the strain and temperature changes, the peak resonant wavelength will also change. Changes in the resonant peaks are measured to determine the strain or temperature measurement. measurement Simulation showed that the relationship between strain and change in peak wavelength is linear with slope (Δλ / ΔF) 1.41 nm / kNewton. Keywords: Extensometer, linear potentiometers, fiber Brag grating, landslides, system monitoring, disaster